Análisis del desempleo y su afectación a las condiciones de vida de los ecuatorianos, período 2019-2021. - Salinas Campuzano, Davis Xavier; Sotomayor Pereira, Jorge Guido (Machala : Universidad Técnica de Machala, 2022)
The objective of this research is to identify how unemployment affects the living conditions of Ecuadorians during the 2019-2021 period. In this sense, the main indicator, unemployment, is taken into account to analyze its behavior and capture its variations. It also seeks to identify the effects on other social and economic indicators such as consumption, poverty, inequality, education, security, income and a business analysis of the 6 main sectors that are service, commerce, agriculture-livestock-forestry and fishing, manufacturing industries, construction and exploitation of mines and quarries. For this, a documentary methodology is applied using statistical data from the National Institute of Statistics and Censuses and the Central Bank, as well as a descriptive approach that allows explaining the behavior of the object of study. The methods used are historical-logical and analytical-synthetic for the theoretical foundation. The results of the research show, during the pandemic year, a drop in investment by -19.0%, an increase in unemployment by 4.9%, a drop in GDP by -7.8%, an increase in income poverty by 33, 0%, increase in inequality by 0.498, drop in national employment to 95.1%, Family income in 746.67, average years of schooling in 10.53 years, increase in intentional homicides by type, raising the figure to 1,372, decrease in consumption by -8.2% all with respect to the previous year. The 3 sectors most affected in 2020 were services with 17,366 closed companies, commerce with 8,596 and the manufacturing industry with 3,816 disabled companies.
La presente investigación tiene por objetivo identificar como el desempleo afecta a las condiciones de vida de los ecuatorianos durante el período 2019-2021. En este sentido se toma en cuenta el indicador principal que es el desempleo para analizar su comportamiento y plasmar sus variaciones. También se busca identificar los efectos hacia otros indicadores sociales y económicos como son el consumo, pobreza, desigualdad, educación, seguridad, ingresos y un análisis empresarial de los 6 sectores principales que son el de servicio, comercio, agricultura-ganadería-silvicultura y pesca, industrias manufactureras, construcción y explotación de minas y canteras. Para aquello se aplica una metodología documental utilizando datos estadísticos del Instituto Nacional de Estadísticas y Censos y Banco Central, además un enfoque descriptivo que permite explicar el comportamiento del objeto de estudio. Los métodos utilizados son el histórico-lógico y analítico-sintético para la fundamentación teórica. Los resultados de la investigación demuestran durante el año pandémico la caída de la inversión en un -19,0%, aumento del desempleo en 4,9%, caída del PIB en -7,8%, incremento de pobreza por ingresos en 33,0%, aumento de la desigualdad en 0,498, caída del empleo nacional a 95,1%, Ingreso familiar en 746,67, años promedio de escolaridad en 10,53 años, incremento de los homicidios intencionales por tipo ascendiendo la cifra a 1.372, disminución del consumo en -8,2% todos con respecto al año anterior. Los 3 sectores más afectados en el 2020 fue el de servicios con 17.366 empresas cerradas, comercio con 8.596 y la industria manufacturera con 3.816 empresas inhabilitadas.
Keywords: DESEMPLEO; CRISIS; REACTIVACION; POBREZA